2005
DOI: 10.1111/j.1525-142x.2005.05007.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the male BmDSX protein in the sexual differentiation of Bombyx mori

Abstract: The sex determination pathway is different between Drosophila melanogaster and Bombyx mori in the initial signal. Here we show evidence that the sex determination pathway in B. mori is similar to that of D. melanogaster at the level of the terminal regulator, doublesex (dsx), which is essential for the proper differentiation of the sexually dimorphic somatic features of D. melanogaster. In B. mori, a homolog of dsx (Bmdsx) is expressed in various tissues, and its primary transcript is alternatively spliced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 50 publications
6
97
0
Order By: Relevance
“…Sexually mosaic individuals have been observed in a wide variety of butterflies and moths (27). In B. mori, a homolog of doublesex, a sex-related gene of D. melanogaster located downstream of the sex determination cascade, is certainly transcribed in a sex-specific manner (36,46). Hence, although the mechanism is unknown, lepidopteran sex determination is probably completed very early in embryogenesis, as in many other insects and animals (7,52).…”
Section: Vol 73 2007 Wolbachia-induced Feminization In a Butterfly mentioning
confidence: 99%
“…Sexually mosaic individuals have been observed in a wide variety of butterflies and moths (27). In B. mori, a homolog of doublesex, a sex-related gene of D. melanogaster located downstream of the sex determination cascade, is certainly transcribed in a sex-specific manner (36,46). Hence, although the mechanism is unknown, lepidopteran sex determination is probably completed very early in embryogenesis, as in many other insects and animals (7,52).…”
Section: Vol 73 2007 Wolbachia-induced Feminization In a Butterfly mentioning
confidence: 99%
“…Also a tra homolog has not been found in the Bombyx genome (Mita et al, 2009). Despite these differences, a B. mori dsx homolog (Bmdsx) has been implicated in sex determination (Suzuki et al, 2005). Bmdsx produces alternatively spliced mRNA isoforms that encode sex specific transcription factors as observed in dsx (Suzuki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Like dsx, the primary transcript of the Bmdsx gene is alternatively spliced in males and females to yield sex-specific mRNAs that encode male-specific (BmDSXM) and femalespecific (BmDSXF) polypeptides (36,42). Transgenic analysis of Bmdsx revealed that Bmdsx functions as a double-switch gene at the final step in the B. mori sex determination cascade (43,44). Despite these similarities between dsx and Bmdsx, the underlying mechanism for sex-specific splicing is clearly different.…”
mentioning
confidence: 99%